Muhammadiyah's Role in Managing Human Trafficking Effort in Timur Lombok Regency, Nusa Tenggara Barat - Widya Hartati; Salmi Yuniar Bahri (IHSA Institute, 2022)
Human trafficking is a form of crime against human dignity and slavery in the modern era whose crimes are often carried out across national borders, victims of human trafficking are not only adults but also victims are minors who are exploited to be employed abroad. Seeing the phenomenon that has occurred, Muhammadiyah's own role is needed to prevent the crime of trafficking in persons. The purpose of this study was to identify and describe the factors behind the occurrence of human trafficking and the role of Muhammadiyah in overcoming human trafficking in the district of East Lombok. The type of research used is qualitative with descriptive method, which is a method that reveals a picture of the problems that occurred during the research. The results of the study reveal that trafficking in persons occurs because of the crush of life's problems and economic needs are not fulfilled, the factors that influence trafficking in persons are due to economic factors and environmental factors, so Muhammadiyah itself must carry out its role and prevention through preaching enlightenment to the public regarding knowledge about the dangers of trafficking in persons, namely by conducting socialization and changing the mindset of families and communities, improving Human Resources (HR) by improving the quality of education from a lower level, namely Elementary School (SD) to a higher level, Providing basic skills training so that people have their own steady income, By implementing entrepreneurship training and access to financial credit to facilitate self-employment.